MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SMAN 1 MAMUJU KECAMATAN MAMUJU KABUPATEN MAMUJU - Rusman Rusman (PINISI :Journal of Teacher Professional, 2022)
This study aims to improve teacher competence in preparing lesson plans (RPP) through ongoing guidance at SMA Negeri 1 Mamuju, Mamuju Regency, West Sulawesi Province. This school action research (PTS) was carried out through two cycles to see an increase in teacher competence in compiling eleven components in the lesson plan. In cycle I (first) all teachers (twelve people) include all components in their lesson plans. In this first cycle, the total score obtained by 12 teachers was 759, divided by 11 components in lesson plans (759/11 = 69), if the percentage was 69%. Whereas in Cycle II all twelve teachers included all components in their lesson plans. In this second cycle, the total score obtained by 12 teachers is 916 divided by 11 components in lesson plans (916/11 = 83), if the percentage is 83%, which means there is an increase of 14% from the first cycle to the second cycle. Overall, all 12 teachers experienced an increase in competence in compiling lesson plans, because all teachers at SMA Negeri 1 Mamuju had included all the components in the lesson plan after going through ongoing guidance from the school principal as the researcher. Data collection techniques in this study were interview techniques, observation and discussion. While the tools used in this study were (1) an interview sheet guide to find out the teacher's initial abilities about lesson plans, (2) Using observation sheets to find out the components of lesson plans that have been or have not been made by the teacher, (3) Discussion, with a view to sharing opinions between researchers and teachers.